The Relationship Between Math Anxiety and Math Performance: A Meta-Analytic Investigation - Zhang, Jing; Zhao, Nan; Kong, Qi Ping (Frontiers in Psychology, 2019)
Math anxiety (MA) has been suggested to decrease the math performance of students. However, it remains unclear what factors moderate this relationship. The purpose of this study was to analyze the link between MA and math performance. Studies that explored the relationship between MA and math performance, conducted from 2000 to 2019 (84 samples, N = 8680), were identified and statistically integrated with a meta-analysis method. The results indicated a robust negative correlation between MA and math performance. Furthermore, regarding the analysis of moderator variables, this negative link was stronger in the studies that involved Asian students, whereas it was the weakest in the studies that involved European students. Moreover, this negative link was stronger in the studies within a senior high school group, whereas it was the weakest in the studies within an elementary group. Finally, this negative link was strongest among studies that used a custom test and studies that assessed problem-solving skills. Potential explanations and implications for research and practice are discussed.